1998
DOI: 10.1128/mcb.18.4.2230
|View full text |Cite
|
Sign up to set email alerts
|

Notch Inhibition of E47 Supports the Existence of a Novel Signaling Pathway

Abstract: E47 is a widely expressed transcription factor that activates B-cell-specific immunoglobulin gene transcription and is required for early B-cell development. In an effort to identify processes that regulate E47, and potentially B-cell development, we found that activated Notch1 and Notch2 effectively inhibit E47 activity. Only the intact E47 protein was inhibited by Notch-fusion proteins containing isolated DNA binding and activation domains were unaffected-suggesting that Notch targets an atypical E47 cofacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
192
2
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(206 citation statements)
references
References 94 publications
(100 reference statements)
11
192
2
1
Order By: Relevance
“…Other Notch target genes are NFkB2 [29], Ifi-202, Ifi-204, Ifi-D3, and ADAM19 [19]. A number of other genes have been reported including Notch1 itself and Notch3 [16], bcl-2 [30] and E2A [31] and HoxA5, 9 and 10 [32].…”
Section: Notch Target Genesmentioning
confidence: 99%
“…Other Notch target genes are NFkB2 [29], Ifi-202, Ifi-204, Ifi-D3, and ADAM19 [19]. A number of other genes have been reported including Notch1 itself and Notch3 [16], bcl-2 [30] and E2A [31] and HoxA5, 9 and 10 [32].…”
Section: Notch Target Genesmentioning
confidence: 99%
“…25 We thus investigated the regulation of the SRG3 expression by Deltex1. By using real-time PCR analysis on 16610D9 cells infected with either retrovirus expressing Deltex1 (S003-Deltex1) or control vector (S003), we found that endogenous SRG3 mRNA was downregulated by Deltex1 (approximately 47% decrease) (Figure 4a).…”
Section: Notchic-activated Deltex1 Represses the Srg3 Expressionmentioning
confidence: 99%
“…26 Moreover, p300 can associate with the bHLH region and the amino-terminal region of E2A proteins. 21,25 Furthermore, Deltex1 was reported to bind directly to p300, thereby counteracting p300-dependent transcriptional activation by bHLH protein. 21 Therefore, we next examined whether both NotchIC and Deltex1 signaling sequesters the E47 away from coactivators such as p300 stimulating E2A transcriptional activation on the SRG3 promoter.…”
Section: Notchic-activated Deltex1 Represses the Srg3 Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some Hes1-Hes5 double-null cells are still inhibited by caNotch-AP infection from differentiating as mature neurons [18], suggesting that Notch can still partially function independently of Hes1 and Hes5. The molecular nature of Hes1-Hes5-independent Notch pathway is a current hot topic [20,21] and remains to be analyzed.…”
Section: Hes1 and Hes5 As Notch Effectorsmentioning
confidence: 99%